2007 IEEE Information Theory Workshop on Information Theory for Wireless Networks 2007
DOI: 10.1109/itwitwn.2007.4318069
|View full text |Cite
|
Sign up to set email alerts
|

A Rank-Metric Approach to Error Control in Random Network Coding

Abstract: It is shown that the error control problem in random network coding can be reformulated as a generalized decoding problem for rank-metric codes. This result allows many of the tools developed for rank-metric codes to be applied to random network coding. In the generalized decoding problem induced by random network coding, the channel may supply partial information about the error in the form of erasures (knowledge of an error location but not its value) and deviations (knowledge of an error value but not its l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 17 publications
(28 reference statements)
0
85
0
Order By: Relevance
“…In [1] a Reed-Solomon-like construction for constant dimension codes was introduced and Silva et al showed that lifting (i.e. concatenating an identity block in front of a matrix and taking the row space) maximum rank distance codes leads to exactly the same codes [4]. The cardinality of Reed-Solomon-like codes is q (n−k)(k−δ+1) for given ambient space dimension n, subspace dimension k and minimum distance 2δ.…”
Section: B Reed-solomon-like Codesmentioning
confidence: 99%
See 1 more Smart Citation
“…In [1] a Reed-Solomon-like construction for constant dimension codes was introduced and Silva et al showed that lifting (i.e. concatenating an identity block in front of a matrix and taking the row space) maximum rank distance codes leads to exactly the same codes [4]. The cardinality of Reed-Solomon-like codes is q (n−k)(k−δ+1) for given ambient space dimension n, subspace dimension k and minimum distance 2δ.…”
Section: B Reed-solomon-like Codesmentioning
confidence: 99%
“…Different approaches of constructing constant dimension codes have been investigated, e.g. in [1], [2], [3], [4], [5] and [6].…”
Section: Introductionmentioning
confidence: 99%
“…Network coding for multicast packet erasure correction was considered in [4], [5]. The problem of multicast noncoherent error correction, where the network topology and/or network code are not known a priori, was studied in [6], [7], [8].…”
Section: A Background and Related Workmentioning
confidence: 99%
“…The second attack model is called Byzantine attacks that attackers may modify the coded packets. To address this problem, Koetter [16] and Kschischang [17] proposed the rank metric error-correcting codes, then extended for the scenario in which the channel may supply partial information about erasures and deviations from the sent information flow [18]. At the same time, some network error correction codes have been proposed in [19][20][21].…”
Section: Introductionmentioning
confidence: 99%